Mobile Application for Locating Nearby Garbage Collection Sites - martinus maslim; Stephanie Pamela Adithama; Aldo Purwanto (Journal of Applied Research In Computer Science and Information Systems, 2023)
Human actions produce waste. The placement of garbage cans is an issue in the Special Region of Yogyakarta. The public is often unaware of the location of garbage cans. The Nearest Garbage Sites Search System (SIPTeST) solves an existing problem. The objective of developing SIPTeST is to enable the public to determine the location of the nearest garbage can based on their current location. SIPTeST is based on both mobile and web platforms. The SIPTeST website is constructed with PHP and MySQL. Android Studio is used to build SIPTeST mobile. In addition to using the user's location, the system uses the user's location to add garbage bin locations. Location-based services (LBS) are implemented by SIPTeST. This system's output is that it assists users in locating the closest garbage cans and viewing photos of their locations. The user can also observe the location history of previously viewed trash cans. Then, users who encounter problems can also submit reports.